THE SHIFTING SANDS OF WASTE: A DECADAL ANALYSIS OF ILLEGAL DUMPING TRENDS AND MITIGATION STRATEGIES IN INDONESIA - Fariz, Reza Darma Al; Muis, Ramdiana; Anggraini, Nani; Matsumoto, Toru (JEBE: Journal of Environment Behavior and Engineering, 2025)
Illegal dumping represents a critical environmental and public health challenge in Indonesia, exacerbated by rapid urbanization, inadequate waste management infrastructure, and socio-cultural attitudes toward waste disposal. This study employs a descriptive literature review methodology to analyze illegal dumping trends over the past decade, synthesizing data from peer-reviewed articles, government reports, and case studies. Findings reveal the proliferation of unauthorized dumpsites, particularly in urban areas, alongside the increasing prevalence of plastic waste as a dominant component. Socio-economic factors such as poverty, limited access to formal waste management systems, and insufficient public awareness are identified as key drivers of this issue. Illegal dumping causes significant environmental degradation, including water contamination and ecosystem disruption, and poses substantial health risks through exposure to hazardous materials and vector-borne diseases. This research underscores the necessity for integrated interventions, highlighting the need for a comprehensive and multi-faceted approach to effectively tackle illegal dumping. Specifically, this entails strengthening regulatory frameworks, enhancing enforcement mechanisms, promoting community engagement, leveraging technological innovations, and making substantial investments in the strategic development of waste management infrastructure.